O trabalho educativo e o profissional de apoio administrativo educacional de Mato Grosso : uma demanda para as Universidades Públicas - Andrade, Guelda Cristina de Oliveira (2015)
The research aims the following theme "The educational work and professional educational administrative support of Mato Grosso: a demand for public universities" in order to search the understanding on how the schooling in superior education reflects in the educational work of the professional educational administrative support (AAE) within the public school of basic education. The methodological procedure of work is anchored in literature, documentary and field, based on the perspective of historical and dialectical materialism. The main theme addresses the role of the university in society, access to this professional training in higher education, the theoretical training and democratic management with emphasis on the role of the AAE in professional school democratic spaces, as well as the concept of educator from the Law No. 12,014 / 09 and educational work. The research presents the referred professional history and the search for training in higher education, the legal frameworks of training that strengthened the process of struggle and achievements in career, it also shows the invisibility of this professional in academic research, above all, defies the Higher Education institutions to offer such training to AAE professional. The survey results depict that they remained without professional training for almost two centuries and even with the assurance of legislation, higher education policy for the AAE professional as well as being insufficient to meet demand, it seems not to have signed the point of view of implementation and their formation direction. The interviews show that the training in higher education reflects both the school universe as in the individual's personal life, it has been aimed at professional development and educational work. The state of Mato Grosso has not developed and / or implemented any focused on vocational training policy in question, between the period 1998 to 2013, beyond the Educator room design, although the union has assumed its role to promote this public policy considering its importance in the context of public school basic education.